2016
DOI: 10.1002/adfm.201600907
|View full text |Cite
|
Sign up to set email alerts
|

Unique Necklace‐Like Phenol Formaldehyde Resin Nanofibers: Scalable Templating Synthesis, Casting Films, and Their Superhydrophobic Property

Abstract: 1D necklace‐like nanostructures have exhibited different potential applications due to their unique geometry and property. However, their macroscopic and controllable synthesis has been a challenge. Herein, a facile and scalable template‐directed hydrothermal process is reported to synthesize a series of necklace‐like phenol‐formaldehyde resin (PFR) wrapped nanocables. The 1D templates involved in the synthesis can be various, such as tellurium nanowires (TeNWs), silver nanowires, and carbon nanotubes. After r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…The various elements produced by these multicomponent conjugants spinning methods are finally dissociated after a subsequent operation (dissolution or splitting process) to obtain nanofibers. A fourth group is dedicated to the methods using an electric field for the development of nanofibers [ 55 ]. They can be described as electrospinning methods.…”
Section: Production Of Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The various elements produced by these multicomponent conjugants spinning methods are finally dissociated after a subsequent operation (dissolution or splitting process) to obtain nanofibers. A fourth group is dedicated to the methods using an electric field for the development of nanofibers [ 55 ]. They can be described as electrospinning methods.…”
Section: Production Of Nanofibersmentioning
confidence: 99%
“…Nanospider™ needle-free technology presented by Elmarco Company is a good example for this purpose. In addition to all these methods, there are some others such as drawing, template synthesis, self-assembly, phase separation, and flash spinning [ 55 , 56 , 57 , 58 , 59 ], but most of them are only limited to the laboratory scale.…”
Section: Production Of Nanofibersmentioning
confidence: 99%
“…In colloidal synthesis, polymers uniformly cladding on nanowires can liquefy and further thermodynamically evolve into periodical shells as driven by the polymer− nanowire−solution three-phase interfacial energy. Such liquefaction and evolution behaviors of polymer shells on 1D nanowires due to Plateau-Rayleigh instability are general and have given rise to an array of periodically shelled nanowires 31,32 (Figure 3c-ii). Intriguingly, we found that this chemical transformation principle is applicable to inorganic superionic conductors.…”
Section: Regiospecific One-off Transformationmentioning
confidence: 99%
“…Moreover, when the glucose was replaced by other carbon sources, many other kinds of carbonaceous shells could be coated on the surfaces of Te NWs. For example, necklace‐like Te@PFR (PFR is the acronym for phenol‐formaldehyde resin) nanocables (Figure (6)) were prepared via a facile and scalable template‐directed hydrothermal process, and Te@N‐doped‐C nanocables (Figure (7)) with a diameter ranging from 40 to 540 nm were successfully obtained by the hydrothermal carbonization of glucosamine hydrochloride (C 6 H 13 NO 5 ·HCl) . Through a similar hydrothermal carbonization process, Te@Fe/N‐codoped‐C with a diameter of 150 nm could be prepared by changing the reaction precursor to ferrous gluconate and the cost‐effective biomass‐derived glucosamine hydrochloride (Figure (8)) …”
Section: G Te Nws and The Derived 1d Nanostructuresmentioning
confidence: 99%